Z dorobku polskiej dialektologii przełomu XX i XXI wieku w zakresie badania gwary lasowskiej - Kowalik, Krystyna (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2018)
The article discusses the latest research regarding the dialect of the Lasowiacy, a subethnic group living at the conflux of the Vistula and the San in southern Poland. These studies are linguistic or ethnographic and verify the current state of the dialect, its stratification and functions in the fluid realities. Some researchers claim the present stage is one of “the emergence of an supraregional interdialect based on the Lasowiacy patois, whose usage encompasses a certain section of Subcarpathia” (Radwański 2013).